2009
DOI: 10.1152/physiol.00042.2008
|View full text |Cite
|
Sign up to set email alerts
|

Re-expression of Locomotor Function After Partial Spinal Cord Injury

Abstract: After a complete spinal section, quadruped mammals (cats, rats, and mice) can generally regain hindlimb locomotion on a treadmill because the spinal cord below the lesion can express locomotion through a neural circuitry termed the central pattern generator (CPG). In this review, we propose that the spinal CPG also plays a crucial role in the locomotor recovery after incomplete spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
13

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 120 publications
0
50
0
13
Order By: Relevance
“…Thus, the animal models allow for deeper insights into sub-hierarchical (less conscious) neuronal control circuits (like neural recordings of central pattern generator activity in spinalized cats) that are, at best, only indirectly or consciously accessible by patients. 36,37 Spatial and temporal aspects Besides looking at principles in neural repair, there are some spatial and temporal aspects of comparisons between human and animal outcomes after SCI that ask for special consideration. The spatial aspects address issues like the total size of the cord, the magnitude of post-traumatic tissue damage (which may eventually evolve to post-traumatic cyst formation), as well as what is the most frequent pattern of cord damage (contusion) and related SCI syndromes, such as anterior cord, central cord or Brown-Sequard syndrome.…”
Section: Translation Of Outcome Measuresmentioning
confidence: 99%
“…Thus, the animal models allow for deeper insights into sub-hierarchical (less conscious) neuronal control circuits (like neural recordings of central pattern generator activity in spinalized cats) that are, at best, only indirectly or consciously accessible by patients. 36,37 Spatial and temporal aspects Besides looking at principles in neural repair, there are some spatial and temporal aspects of comparisons between human and animal outcomes after SCI that ask for special consideration. The spatial aspects address issues like the total size of the cord, the magnitude of post-traumatic tissue damage (which may eventually evolve to post-traumatic cyst formation), as well as what is the most frequent pattern of cord damage (contusion) and related SCI syndromes, such as anterior cord, central cord or Brown-Sequard syndrome.…”
Section: Translation Of Outcome Measuresmentioning
confidence: 99%
“…Given their widespread projections, these cells may participate in the coordination between limbs as well as in weight support directly or as an integrative relay between the cortex and spinal cord. 13 Besides these pathways, it is clear that on lesion type AIS B, patients have a certain grade of sensation that means that they have some dorsal pathways preserved. In rats, it has been observed that lesions at the Rubrospinal nucleus cause persistent deficits during over ground and skilled locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, it has been observed that lesions at the Rubrospinal nucleus cause persistent deficits during over ground and skilled locomotion. 13 Hence preservation of this nucleus is a conceivable condition needed to initiate locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…Grasso et al 8 reported that locomotor responses elicited by treadmill training in SCI patients may depend on a plastic redistribution of activity across most of the rostrocaudal extent of the spinal cord. Rossignol et al 15 reviewed the role of CPG in locomotor recovery after incomplete SCI. It has been recognized that partial body weight support with the loading of weight on the hind feet is important for locomotor training.…”
Section: Central Pattern Generatormentioning
confidence: 99%